Ultrafast Relaxation Rates and Reversal Time in Disordered Ferrimagnets - Altbir-Drullinsky, D (American Physical Society, 2015)
In response to ultrafast laser pulses, single-phase metals have been classified as "fast" (with magnetization quenching on the time scale of the order of 100 fs and recovery in the time scale of several picoseconds and below) and "slow" (with longer characteristic time scales). Disordered ferrimagnetic alloys consisting of a combination of "fast" transition (TM) and "slow" rare-earth (RE) metals have been shown to exhibit an ultrafast all-optical switching mediated by the heat mechanism. The behavior of the characteristic time scales of coupled alloys is more complicated and is influenced by many parameters such as the intersublattice exchange, doping (RE) concentration, and the temperature. Here, the longitudinal relaxation times of each sublattice are analyzed within the Landau-Lifshitz-Bloch framework. We show that for moderate intersublattice coupling strength both materials slow down as a function of slow (RE) material concentration. For larger coupling, the fast (TM) material may become faster, while the slow (RE) one is still slower. These conclusions may have important implications in the switching time of disordered ferrimagnets such as GdFeCo with partial clustering. Using atomistic modeling, we show that in the moderately coupled case, the reversal would start in the Gd-rich region, while the situation may be reversed if the coupling strength is larger. © 2015 American Physical Society.